LATE CHALCOLITHIC CERAMIC DEVELOPMENT IN SOUTHERN IRAQI KURDISTAN: THE STRATIGRAPHIC SOUNDING AT KANI SHAIE. (December 2021) - Renette, Steve; Jayyab, Khaled Abu; Gibbon, Elizabeth; Lewis, Michael P.; Abdullkarim Qadir, Zana; Cabral, Ricardo; Tomé, André G.
Abstract : Kani Shaie is a small archaeological site in the Kurdistan Region of Iraq, centrally located in the Bazian Basin, a narrow valley at the western edge of the Zagros Mountains along the major route between Kirkuk and Sulaymaniyah. Its main mound was inhabited almost continuously from the fifth to the middle of the third millennium, c. 5000–2500 B.C.E. This period of Mesopotamian prehistory, corresponding to the Chalcolithic and Early Bronze Age, witnessed major transformations such as initial urbanism and intensification of interregional interaction networks. The recent resurgence of fieldwork in the Kurdistan Region of Iraq is beginning to reveal local trajectories that do not always match the established chronological framework, which is largely based on changes in ceramic technology and styles observed in northern Mesopotamia. Here, we discuss the ceramic sequence retrieved from a step trench at Kani Shaie spanning the entire Late Chalcolithic (c. 4600–3100 B.C.E.). A bottom-up approach to potting traditions at the site allows an initial assessment of the relationship between local communities in the Zagros foothills and large-scale developments in the Mesopotamian world. We argue that the evidence from Kani Shaie reflects a long process in which different communities of practice made active choices of adopting, adapting, or rejecting non-local cultural practices.